2000
DOI: 10.1002/1097-0215(20000901)87:5<615::aid-ijc1>3.0.co;2-4
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular P-glycoprotein expression is associated with the intrinsic multidrug resistance phenotype in human colon adenocarcinoma cells

Abstract: The 2 clones, LoVo 5 and LoVo 7, derived from untreated LoVo WT human colon adenocarcinoma cells and exhibiting different sensitivity to doxorubicin (DOX), were compared in order to identify possible determinants of intrinsic drug resistance. A multidrug resistant variant cell line, selected from LoVo WT cells by continuous exposure to DOX (LoVo DX), was also included in the study. Analysis of the expression and organization of cytoskeletal elements by flow cytometry and fluorescence microscopy evidenced a pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 65 publications
(37 citation statements)
references
References 33 publications
(33 reference statements)
1
36
0
Order By: Relevance
“…23 LoVo DX cells were about 100 times more resistant to DOX treatment than LoVo WT cells. Concerning the surface P-gp expression examined by flow cytometry, LoVo WT cells were negative while MDR variants were strongly positive for P-gp labeling.…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…23 LoVo DX cells were about 100 times more resistant to DOX treatment than LoVo WT cells. Concerning the surface P-gp expression examined by flow cytometry, LoVo WT cells were negative while MDR variants were strongly positive for P-gp labeling.…”
Section: Resultsmentioning
confidence: 96%
“…Cell suspensions were then incubated for 30 min at 4°C with MAb MRK16 (Kamiya, Seattle, WA). 23 The intracellular content of thiol groups was determined using CM-H 2 DCFDA (Molecular Probes, Eugene, OR). 28 CM-H 2 DCFDA stocks (10 mM) were prepared in ethanol.…”
Section: Flow Cytometrymentioning
confidence: 99%
See 1 more Smart Citation
“…66,69 Several studies have suggested that intracellular P-gp also contributes to drug resistance. 58,70 Indeed, studies using leukemic cell lines and AML patient samples have shown that the levels of total P-gp (protein or mRNA) correlated better with drug efflux than those of surface P-gp protein. 69 Furthermore, a strong association between intracellular P-gp and intrinsic resistance was observed in a human colon carcinoma clone, which did not express P-gp on the plasma membrane.…”
Section: P-gp Synthesis Cellular Localization Expression and Functionmentioning
confidence: 99%
“…69 Furthermore, a strong association between intracellular P-gp and intrinsic resistance was observed in a human colon carcinoma clone, which did not express P-gp on the plasma membrane. 70 Nevertheless, other studies claim that intracellular P-gp does not seem to have a (major) role in drug resistance. 61,64 Therefore, it is important to better understand how P-gp is regulated, which seems to be a complex and highly controlled process.…”
Section: P-gp Synthesis Cellular Localization Expression and Functionmentioning
confidence: 99%